2022
DOI: 10.1038/s41467-022-34395-2
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer single-cell analysis reveals the heterogeneity and plasticity of cancer-associated fibroblasts in the tumor microenvironment

Abstract: Cancer-associated fibroblasts (CAFs) are the predominant components of the tumor microenvironment (TME) and influence cancer hallmarks, but without systematic investigation on their ubiquitous characteristics across different cancer types. Here, we perform pan-cancer analysis on 226 samples across 10 solid cancer types to profile the TME at single-cell resolution, illustrating the commonalities/plasticity of heterogenous CAFs. Activation trajectory of the major CAF types is divided into three states, exhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
151
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(163 citation statements)
references
References 95 publications
11
151
1
Order By: Relevance
“…Inflammatory CAFs and ECM CAFs show enhanced invasive activity and mobilize surrounding immune cells to construct a tumor-friendly microenvironment, which is associated with poor prognosis of GC. Recently, a pan-cancer single-cell analysis reveal the heterogeneity of CAF and revealed their different activation pathways and roles (46). The article proposed that a high proportion of FAP+ CAFs was significantly associated with poor OS, which was similar to the conclusion obtained in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Inflammatory CAFs and ECM CAFs show enhanced invasive activity and mobilize surrounding immune cells to construct a tumor-friendly microenvironment, which is associated with poor prognosis of GC. Recently, a pan-cancer single-cell analysis reveal the heterogeneity of CAF and revealed their different activation pathways and roles (46). The article proposed that a high proportion of FAP+ CAFs was significantly associated with poor OS, which was similar to the conclusion obtained in our study.…”
Section: Discussionsupporting
confidence: 88%
“…The fact that we were able to define almost all CAF phenotypes in datasets from multiple cancer types, both when analysed individually and when analysed as an integrated dataset, strongly suggests that CAF phenotypes are generalizable across cancer types. A recent pan-cancer study has compared plasticity of fibroblasts and showed that distinct features are shared between the different tumour sites 39 .This may extend also to subtypes; for example, our breast cancer dataset mainly consisted of luminal B cancer, but the CAF phenotypes we defined were also present in samples of the other subtypes. Still, our data also indicate that different cancer types may be dominated by different CAF types.…”
Section: Discussionmentioning
confidence: 71%
“…Since we showed that time-resolved wound signatures could act as markers for whole tumor states, it is possible that genes that are overexpressed in wound fibroblasts at different phases of healing could act as markers for CAF subtypes, which are highly heterogeneous within and across tumor types [22, 23]. Therefore, we first correlated the inflammatory, proliferative and resolution phase wound genes with the gene expression signatures of wound fibroblasts from different phases of healing by re-analyzing the transcriptomes of wound fibroblasts from early- and late-stage large excisional mouse wounds [24] (Table S1).…”
Section: Resultsmentioning
confidence: 99%